Tingkat Kesesuaian Antara Posisi dan Job Deskripsi Karyawan di Perusahaan Jaya Abadi Motor pada Tahun 2024 dalam Perspektif Sosiologi Organisasi - Triana Rahmawati; Yuanita Dwi Hapsari; Aisya Lu'luil Maknun; Salsabila Putri Chaerunnisa (Jurnal Community, 2025)
This study aims to analyze the alignment between employees’ positions and job descriptions at Toko Jaya Abadi Motor, Sragen, using Alo Liliweri’s organizational sociology perspective. Compatibility between positions and job descriptions is crucial for maintaining employee performance, job satisfaction, and organizational stability. A mixed-methods approach with a descriptive design was employed, involving 23 employees as respondents through interviews and a questionnaire consisting of 43 Likert-scale items. The results of the study indicate that Toko Jaya Abadi Motor has a stable level of alignment between employees’ positions and their job descriptions. The leadership system implemented is a centralized leadership structure, in which the store owner serves as the primary decision-maker. Employee performance remains relatively stable due to social cohesion, although variations in individual initiative were observed. Employee motivation is driven by both economic and socio-emotional factors, with job satisfaction strongly supported by a familial work atmosphere. Nevertheless, the absence of formal SOPs and limited career development opportunities are significant challenges. These findings highlight that the success of small and medium enterprises (SMEs) is largely influenced by internal social dynamics rather than formal managerial efficiency